Probiotic-loaded microcapsule system for human in situ folate production: Encapsulation and system validation - Ramos, Philippe Emmanuel Cruz (2016)
This study focused on the use of a new system, an alginate | -poly-l-lysine | alginate | chitosan microcapsule (APACM), able to immobilize a folate-producing probiotic, Lactococcus lactis ssp. cremoris (LLC), which provides a new approach to the utilization of capsules and probiotics for in situ production of vitamins. LLC is able to produce 95.25 ± 26 g·L 1 of folate, during 10 h, and was encapsulated in the APACM. APACM proved its capacity to protect LLC against the harsh conditions of a simulated digestion maintaining a viable concentration of 6 log CFU·mL 1of LLC. A nutrients exchange capacity test, was performed using Lactobacillus plantarum UM7, a high lactic acid producer was used here to avoid false negative results. The production and release of 2 g·L 1 of lactic acid was achieved through encapsulation of L. plantarum, after 20 h. The adhesion of APACM to epithelial cells was also quantified, yielding 38% and 33% of capsules adhered to HT-29 cells and Caco-2 cells, respectively.